1986
DOI: 10.1088/0031-8949/33/6/006
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Development of the E × B-Instability in the Adiabatic Approximation

Abstract: The nonlinear development of the E × B-instability in a weakly ionized plasma is governed by an infinite set of coupled ordinary nonlinear differential equations for the amplitudes of the modes of the system. The solution of these equations are investigated in the adiabatic approximation by setting the time derivative of linearly stable modes equal to zero. Approximate analytical solutions for the time development of the different modes, in good agreement with previous numerical results, have been obtained for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…Results similar to those obtained by Borei with sea urchin and starfish eggs were reported earlier by Holter and Zeuthen (112) for unfertilized eggs of Ciona intestinalis. Results similar to those obtained by Borei with sea urchin and starfish eggs were reported earlier by Holter and Zeuthen (112) for unfertilized eggs of Ciona intestinalis.…”
Section: Unfertilized Eggsupporting
confidence: 91%
See 1 more Smart Citation
“…Results similar to those obtained by Borei with sea urchin and starfish eggs were reported earlier by Holter and Zeuthen (112) for unfertilized eggs of Ciona intestinalis. Results similar to those obtained by Borei with sea urchin and starfish eggs were reported earlier by Holter and Zeuthen (112) for unfertilized eggs of Ciona intestinalis.…”
Section: Unfertilized Eggsupporting
confidence: 91%
“…The rate of respiration in fertilized sea urchin eggs (Fig. An exponential increase in respiration is also found in Chaetoptem (295) and Ciona ( 112). Lindahl (151) found that after the "exponential" period the curve arrives a t a plateau, but that shortly before the first sign of gastrulation the rate of respiration begins to increase again, although now as a linear function of time.…”
Section: Unfertilized Eggmentioning
confidence: 69%
“…Direct evidence of hydrogen penetration into internal pores was obtained by Holter et.al [34][35][36][37][38] only. He studied a process of hydrogen saturation of metallic samples through temperature spectra of internal friction (at frequencies 200-300 Hz, i.e.…”
Section: Solid Hydrogen In Pores Of Metalsmentioning
confidence: 99%
“…Fig.8. Comparison of temperature dependencies of Q -1 for hydrogen saturated sample and the basic (not saturated) one [34][35][36][37][38].…”
Section: Solid Hydrogen In Pores Of Metalsmentioning
confidence: 99%
See 1 more Smart Citation